GAMBARAN PERAWATAN DIRI ANAK REMAJA PENYANDANG AUTISM SPECTRUM DISORDER DI ASRAMA - Lisa Noviana Savitri; Windy Rakhmawati; Citra Windani Mambang Sari (LPPM STIKES Muhammadiyah Kendal, 2021)
Adolescents with ASD who are living in dormitory with only the assistance of caregivers and without the presence of parents are demanded to be more independent in self-care. Complex disorders that occur in children with Autism Spectrum Disorder (ASD) affect the child's self autonomy to fulfill self-care needs. This study aims to identify the description of self-care agency in adolescents with ASD who are living in dormitory of SLB “X” in Bandung District.This research used a quantitative descriptive design. The sample in this study was adolescents with ASD who are living in dormitory, used total sampling technique with the total of 35 people. The instrument of this study was Kenny Self Care Evaluation (KSCE) which was analyzed and presented in tabular form using frequency distribution in percentage.The results showed that in personal hygiene (74.3%) and toileting (71.4%) of respondents experienced total dependence. In transfer activities (77.1%), dressing (65.7%), and feeding (82.9%) of respondents needed minimal assistance or supervision. However, in activities in bed and locomotion all respondents were independent. The conclusion from this study shows that adolescents with ASD experienced the lowest level of independence where they needed total support in carrying personal hygiene and toileting activities. Thus, it is essential for school and dormitory managers to work closely with community nurses to improve adolescent's skills in self-care by providing education to both adolescents and caregivers.